NOTA SOBRE LA PRESENCIA DE LYCOPSIDAE ARBORESCENTES EN EL PÉRMICO (SERIE INDEPENDENCIA) DEL PARAGUAY (Ameghiniana, 2013)
In the present paper some fragmentary impressions of arborescent Lycopsidae are described. No sistematic assignament is possible, although ir is supposed that they may belong to the Sigillariaceae (?). Additionally, a small profile from the finding place is given, and a few remarks on the general lithology and outcrops of the Permian sediments from Southeastern Paraguay are made.